Determinación de la presencia de residuos antibióticos en leche cruda para el consumo en la ciudad de Loja - Torres Michay, Jessica Elizabeth (2018)
The milk is the pure food most next the perfection, is beneficial for the persons for his multifaceted supplement providing several hours of supply and satiety; the disadvantage appears when, for the utilization of antibiotics to restore the health of the bovine ones the milk would be causing alterations in the human being that they put in danger his health. For this reason, the present investigation tries to determine the presence of antibiotic residues in raw milk destined for the human consumption in Loja's city, constituting a possible problem is to the health of the consumers. In the present study of descriptive type of transverse court, there decided the presence of residues of antibiotics in 68 samples of raw milk bovine proceeding from 4 markets of the city: Small producing market, Mercado Central, Bought San Sebastian and Market Great Colombia. The samples were analyzed in the Pilot Plant of Processing of Lacteal of Loja's National University, using the method of union to recipients kit Trisensor recommended in the Manual of procedures for the vigilance and control of the innocuousness of raw milk (Agrocalidad, 2013). The obtained results indicated that of 68 analyzed samples 7 % presented positive results for residues of antibiotics, specifically for betalactámicos of were coming from the market Great Colombia; of the Central market since from the small producing market they were coming 1 sample with antibiotic residues. These results indicate that there is a population exposed to these pollutants, being able to appear a resistance to antibiotics (Aroca, 2016).